Einführung - Effinger, Maria; Kohle, Hubertus (Die Zukunft des kunsthistorischen Publizierens, 2021)
Maria Effinger is Head of Publication Services at Heidelberg University Library, Managing Director of Heidelberg University Publishing (heiUP), subject specialist for art history (arthistoricum.net), co-spokesperson NFDI4Culture. Main focus: Electronic publishing in open access, digital editions, cultural heritage and digital humanities. https://orcid.org/0000-0001-6396-4876Hubertus Kohle is an art historian at the LMU Munich and works primarily on German and French art from the 18th to the early 20th century.https://orcid.org/0000-0003-3162-1304